2019
DOI: 10.1101/626812
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of siRNA silencing on the susceptibility of the fish cell line CHSE-214 toYersinia ruckeri

Abstract: AbstractBacterial pathogens are known to co-opt mechanisms of the host cells’ physiology to gain intracellular entrance. Among the facultative intracellular bacteria is Yersinia ruckeri, an enterobacterium mostly known as the causative agent of enteric redmouth disease in salmonid fish. In the present study, we applied RNA inhibition to silence twenty pre-selected genes on the genome of a fish cell line (CHSE-214) followed by a gentamycin assay to qua… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…However, like Y. enterocolitica and Y. pseudotuberculosis, it is a known facultative intracellular pathogen 3,4 . Recently, it was shown that silencing of the integrin β-1 precursor in an in-vitro culture of Chinook Salmon embryo cell culture (CHSE) resulted in a significant reduction of the cells' suceptibility to invasion by Y. ruckeri 44 and it is therefore very plausible that Y. ruckeri can make use of the zipper mechanism to invade host cells. In this context, the fact that several adhesion molecules, and in particular integrin molecules were detected at a lower level was unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…However, like Y. enterocolitica and Y. pseudotuberculosis, it is a known facultative intracellular pathogen 3,4 . Recently, it was shown that silencing of the integrin β-1 precursor in an in-vitro culture of Chinook Salmon embryo cell culture (CHSE) resulted in a significant reduction of the cells' suceptibility to invasion by Y. ruckeri 44 and it is therefore very plausible that Y. ruckeri can make use of the zipper mechanism to invade host cells. In this context, the fact that several adhesion molecules, and in particular integrin molecules were detected at a lower level was unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Some bacterial pathogens like Mycobacterium tuberculosis (MTB), Listeria monocytogenes, Mycobacterium fortuitum, S. typhimurium, and Yersiniaceae need host cell facilities for entry and invasion (Agaisse et al, 2005). Inactivating the invasion related genes like SEC22A, Rab1B, and VPS33B by siRNA can prevent bacterial cell entrance to the host cells (Menanteau-Ledouble et al, 2020). In our recent in vitro study, we designed specific siRNA against urease B subunit (ureB) and cytotoxinassociated gene A (CagA) genes from Helicobacter pylori.…”
Section: Bacterial Infectionmentioning
confidence: 99%
“…Menanteau-Ledouble et al, reported that siRNA targets and silence zipper and trigger processes related to genes in Yersinia ruckeri, the causative agent of enteric red mouth in fish. They reported that Rab1A, myotubularin, Lama2, and Rac1 were more strongly silenced by siRNA (Criss and Casanova, 2003;Menanteau-Ledouble et al, 2020). Silencing of Caveolin-2 as a host gene involved in the invasion of Pseudomonas aeruginosa by siRNAs leads to the reduction of bacterial pathogenesis (Zaas et al, 2005).…”
Section: Bacterial Infectionmentioning
confidence: 99%